Sudan : Final Review Under the Medium-Term Staff-Monitored Program and the 2002 Program-Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Sudan's Final Review Under the Medium-Term Staff-Monitored Program (SMP) and the 2002 Program. Sudan has made substantial progress over the past five years of SMPs in achieving macroeconomic stability and advancing structural reforms. The program for 2002 represents a strong and credible effort to bring economic policies back on track, reinforce macroeconomic stability, and meet the challenges of weak external environment. The introduction of mechanisms for greater exchange rate flexibility and for saving oil revenues is particularly welcome.